2019
DOI: 10.1097/aog.0000000000002990
|View full text |Cite
|
Sign up to set email alerts
|

Examining Disparities in Route of Surgery and Postoperative Complications in Black Race and Hysterectomy

Abstract: Objective: To estimate the associations between race, route of hysterectomy and postoperative complications among women undergoing benign hysterectomy. Methods: A cohort study was performed. All patients undergoing benign hysterectomy, recorded in the National Surgical Quality Improvement Program (NSQIP) and its targeted hysterectomy file in 2015, were identified. The primary exposure was patient race. The primary outcome was route of hysterectomy and the secondary outcome was postoperative complication. Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 22 publications
4
71
0
Order By: Relevance
“…Studies, including our prior work, have reported that non-White women, and Black women in particular, are less likely to undergo MIGS [5,[9][10][11][12] and have worse post-operative outcomes, even after controlling for surgical approach [5,[9][10][11]. It is possible, however, that reported differences in outcomes can be explained, at least partially, by pre-existing conditions not controlled for in prior studies and hospital factors not accounted for.…”
Section: Introductionmentioning
confidence: 76%
“…Studies, including our prior work, have reported that non-White women, and Black women in particular, are less likely to undergo MIGS [5,[9][10][11][12] and have worse post-operative outcomes, even after controlling for surgical approach [5,[9][10][11]. It is possible, however, that reported differences in outcomes can be explained, at least partially, by pre-existing conditions not controlled for in prior studies and hospital factors not accounted for.…”
Section: Introductionmentioning
confidence: 76%
“…Prior research suggests women with fewer resources and more comorbidities are more likely to receive a hysterectomy [28]. Further, there is compelling evidence that patients with higher income, private insurance, and white race are more likely to undergo laparoscopic hysterectomy versus open hysterectomy [19,21,29]. These trends are increasingly visible in inpatient endometriosis care.…”
Section: Discussionmentioning
confidence: 99%
“…Slow but steady response to this recommendation is evident; for example, the share of hysterectomies performed laparoscopically increased from 10% in 1997 to 29% in 2010 and 43% in 2013 [1820]. A recent study of the American College of Surgeons National Surgical Quality Improvement Program database found that 30% of recorded hysterectomies for benign indications in 2015 were abdominal, while 16% were vaginal and 55% were laparoscopic [21]. The move towards minimally invasive gynecologic surgery has led to a greater proportion of outpatient procedures, shorter hospital stays, fewer complications, and faster recovery for patients [22], though inpatient surgery remains necessary for some patients.…”
Section: Introductionmentioning
confidence: 99%
“…This study found that racial disparities in MIH no longer persisted within this integrated health care system, unlike in other settings within the United States. 1,5,6 The study by Alexander et al 5 found that African American individuals were approximately twice as likely to undergo open abdominal hysterectomies vs MIHs compared with their white counterparts. The study by Pollack et al 6 demonstrated that despite increasing annual laparoscopic rates, racial/ethnic minority women were less likely to undergo MIH.…”
Section: Discussionmentioning
confidence: 99%
“…Our results may be due to system changes. 4,5 Our initiative increased MIH rates and the proportion of high-volume surgeons while simultaneously reducing the surgeon pool. With these system changes, we observed a reduction of racial disparities in MIH.…”
Section: Discussionmentioning
confidence: 99%